Privacy right in electronic personal data: a jurisprudential consideration (2011)
The breakthrough in information technology has brought about multiplied means of gathering and storing information about individuals and corporate persons likewise. Many personal data come to be in possession of some custodians who, though legally acquired such information, may tend to use them for purposes which are illegal or not within the contractual terms of collecting such information in the first place. Information is also illegally garnered from the information environment to be utilized for illicit or unauthorised purposes. Personal information has been seen to be a personal property by some scholars, which culminates into a right that should be protected by the law while some take a contrary view. However, some nations have seen the need to protect personal information in this relatively new information society as a personal right which should not be infringed upon. This work puts Nigeria into perspective as regards the legal measures taken, if any, for the protection of privacy right in electronic personal data.